2015
DOI: 10.5657/fas.2015.0143
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Dietary Vitamins C and E on Methylmercury-Induced Toxicity in Juvenile Olive Flounder Paralichthys olivaceus

Abstract: This experiment was conducted to evaluate the synergistic effects of vitamin C and E on methylmercury (MeHg) toxicity in juvenile olive flounder Paralichthys olivaceus. In a 3×3 factorial design, 9 experimental diets containing three different vitamin C (0, 200 or 400 mg/kg diet in the form of l-ascorbyl-2-monophosphate) and vitamin E (0, 100 or 200 mg/kg diet in the form of dl-α-tocopheryl acetate) levels with the Hg toxicity level (20 mg/kg diet in the form of MeHg) were formulated. Triplicate groups of fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Numerous studies done with various biological models such as broiler chickens, fish, rats, and other animals have shown that taking exogenous antioxidants such as vitamins C and E can improve health against the damage caused by heavy metals (Park et al, 2015;Hashem et al, 2021;Poli et al, 2022). This has been proved also in the current research, where the administration of vitamins C and E has mitigated the damage caused by exposure to heavy metals.…”
Section: Discussionmentioning
confidence: 52%
“…Numerous studies done with various biological models such as broiler chickens, fish, rats, and other animals have shown that taking exogenous antioxidants such as vitamins C and E can improve health against the damage caused by heavy metals (Park et al, 2015;Hashem et al, 2021;Poli et al, 2022). This has been proved also in the current research, where the administration of vitamins C and E has mitigated the damage caused by exposure to heavy metals.…”
Section: Discussionmentioning
confidence: 52%